Pursuing the concept of existence in the designs of civic centers: the 17th–18th – century Persia - Shahani, Mohammadhossein (Journal of Architecture and Urbanism, 2019)
In recent decades, the concept of existence is increasingly becoming a significant subject in contemporary studies of architecture. However, its concerns in architecture cannot be denied in the last centuries. In the 17th-century Persia, a philosophical movement had effects on the concept of existence, which coincided with the urban developments, and the establishment of novel civic centers. With respect to philosophical backgrounds of architecture, this study aims to interpret the concept of existence in the designs of civic centers. For this purpose, the primacy of existence to essence, and bestowing of presence are illustrated to analyze the presentations in the designs of civic centers in that era. Then, the presentations are categorized to elucidate manifesting units in the designs of civic centers. Finally, the result of this study presents principles applied in the designs of civic centers, based on the concept of existence.